Battery and electronic equipment

By adding the first lithium salt to the positive electrode active material layer of the lithium-ion battery and adding the second lithium salt to the electrolyte solution to form a composite electrolyte membrane, the performance problems of the lithium-ion battery in high and low temperature environments are solved, and the cycling performance and low-temperature discharge performance of the battery are significantly improved.

CN119742421AActive Publication Date: 2025-04-01SHENZHEN HIGHPOWER TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411943542.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-04-01
Estimated Expiration
2044-12-24

Smart Images

  • Figure BDA0005213731860000021
    Figure BDA0005213731860000021
  • Figure BDA0005213731860000031
    Figure BDA0005213731860000031
  • Figure BDA0005213731860000081
    Figure BDA0005213731860000081
Patent Text Reader

Abstract

The invention relates to a battery and electronic equipment. The battery comprises a positive plate, a negative plate, a diaphragm and an electrolyte, the positive plate comprises a positive current collector and a positive active material layer arranged on at least one surface of the positive current collector, the positive active material layer comprises a positive active material, a conductive agent, an adhesive and a positive additive, and the positive additive comprises a first lithium salt; the electrolyte comprises an organic solvent, an electrolyte lithium salt and an electrolyte additive, the electrolyte lithium salt or the electrolyte additive comprises a second lithium salt, and the second lithium salt is the same as or different from the first lithium salt. According to the scheme provided by the invention, the battery can present excellent high and low temperature performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to batteries and electronic devices. Background Art

[0002] Lithium-ion batteries are widely used in 3C digital, power tools, aerospace, energy storage, power vehicles and other fields due to their advantages such as high specific energy, no memory effect and long cycle life. The rapid development of electronic information technology and consumer products has put forward higher requirements for the high voltage and high energy density of lithium-ion batteries.

[0003] In the related technology, ternary positive electrode materials are widely used in portable electronic devices such as mobile phones and laptops, as well as electric vehicles and large energy storage devices due to their advantages such as high energy density, environmental friendliness and long cycle life. However, as the limiting voltage of ternary positive electrode materials continues to increase (especially 4.3V+), the oxidation of electrolyte by ternary positive electrode materials is strengthened, the high temperature performance of the battery is seriously deteriorated, and the long cycle life cannot be guaranteed. Especially during the long-term cycle charge and discharge process under high voltage, the volume of the positive electrode material will expand and cause serious cracks, and the solvent in the electrolyte will enter the interior of the positive electrode material, causing problems such as oxidation of the electrolyte and gas production, which will eventually cause serious capacity decay problems, and the degradation of electrochemical performance will be further aggravated in high temperature environments. In a low temperature working environment, the viscosity of the electrolyte will increase, resulting in a slower lithium ion migration rate and an increase in the battery interface impedance, which will reduce the conductivity of the battery, and ultimately lead to a decrease in the low temperature discharge performance of the battery.

[0004] Therefore, it is urgent to develop a lithium-ion battery with excellent high and low temperature performance. Summary of the invention

[0005] In order to solve or partially solve the problems existing in the related art, the present application provides a battery and an electronic device, which can improve the high and low temperature performance of the battery.

[0006] In a first aspect, the present application provides a battery, wherein the battery comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, the positive electrode active material layer comprises a positive electrode active material, a conductive agent, a binder and a positive electrode additive, and the positive electrode additive comprises a first lithium salt;

[0007] The electrolyte includes an organic solvent, an electrolyte lithium salt and an electrolyte additive. The electrolyte lithium salt or the electrolyte additive includes a second lithium salt, which is the same as or different from the first lithium salt.

[0008] The battery as described above, wherein the second lithium salt is the same as the first lithium salt;

[0009] The electrolyte lithium salt includes a second lithium salt, and the second lithium salt includes lithium hexafluorophosphate; and / or,

[0010] The electrolyte additive includes a second lithium salt, and the second lithium salt includes at least one of lithium difluorophosphate, lithium fluoride, lithium bis(oxalatoborate), lithium tetrafluoroborate, lithium difluorobis(oxalatoborate), lithium difluorobis(oxalatophosphate), lithium tetrafluorobis(oxalatophosphate), lithium carbonate, lithium nitrate, lithium phytate, 4,5-dicyano-2-trifluoromethylimidazole lithium, lithium hexafluoroarsenate, lithium perchlorate, trifluorosulfonyl lithium, bis(trifluoromethylsulfonyl)methyl lithium, and bis(fluorosulfonyl)imide lithium.

[0011] The battery as described above, wherein the second lithium salt includes at least one of lithium difluorophosphate, lithium bis(oxalatoborate), lithium tetrafluoroborate, lithium difluorobis(oxalatoborate), lithium difluorobis(oxalatophosphate), lithium tetrafluorobis(oxalatophosphate), 4,5-dicyano-2-trifluoromethylimidazole lithium, lithium bis(trifluoromethylsulfonyl)imide, and tris(trifluoromethylsulfonyl)methyllithium.

[0012] The battery as described above, wherein the mass percentage of the first lithium salt in the positive electrode active material layer is 0.01% to 1%; and / or,

[0013] The mass percentage of the second lithium salt in the electrolyte is 0.01% to 1%.

[0014] In the battery as described above, the electrolyte additive further comprises a cyclic additive.

[0015] The battery as described above, wherein the cyclic additive comprises at least one of the compounds represented by structural formula 1-1 to structural formula 1-6:

[0016]

[0017]

[0018] And / or, the mass percentage of the cyclic additive in the electrolyte is 0.1% to 4%.

[0019] In the battery as described above, the first lithium salt, the second lithium salt and the cyclic additive satisfy the following relationship:

[0020] 0.01≤M b / M a1 ≤400;

[0021] and / or, 0.005≤M b / (M a1 +M a2 )≤200

[0022] Wherein, the mass percentage of the cyclic additive in the electrolyte is M b %, and the mass percentage of the first lithium salt in the positive electrode active material layer is M a1 %, and the mass percentage of the second lithium salt in the electrolyte is M a2 %.

[0023] In the battery as described above, the first lithium salt, the second lithium salt and the cyclic additive satisfy the following relationship:

[0024] 5≤M b / M a1 ≤60;

[0025] and / or, 0.22≤M b / (M a1 +M a2 )≤12.

[0026] The battery as described above, wherein 0.01≤M a1 ≤1; and / or, 0.01≤M a2 ≤1; and / or, 0.1≤M b ≤4.

[0027] A second aspect of the present application provides an electronic device, which includes the battery as described above.

[0028] The technical solution provided by the present application may include the following beneficial effects: when a first lithium salt is added to the positive electrode sheet, the first lithium salt can decompose on the surface of the positive electrode active material layer to produce lithium-containing compounds, and these substances can participate in the construction of the CEI film, effectively improving the thermal stability, toughness and lithium conductivity of the CEI film, thereby reducing the side reactions between the positive electrode active material and the electrolyte, avoiding the dissolution and structural destruction of the positive electrode active material, and preventing the oxidation and gas production of the electrolyte, thereby improving the cycle performance and storage performance and thermal safety performance of the battery at high temperatures. At the same time, the lithium fluoride rich in the CEI film can enhance the rapid transmission of lithium ions on the positive electrode surface and improve the low-temperature performance of the battery; when a second lithium salt is added to the electrolyte, the second lithium salt not only participates in the construction of the CEI film, but also participates in the construction of the SEI film, thereby simultaneously improving the CEI film of the battery. The thermal stability, toughness and lithium conductivity of the SEI film are improved, the probability of side reactions between the electrolyte and the positive and negative active materials is reduced, the decomposition and gas production of the electrolyte and the structural changes of the positive and negative active materials are avoided, the transmission rate and migration rate of lithium ions are increased, and the high and low temperature performance of the battery is improved; the present application adds the lithium salt separately to the positive electrode active material and the electrolyte, which can solve the problem of low solubility of the lithium salt in the electrolyte, achieve high-content use, and give full play to the performance of the lithium salt. Moreover, the lithium salt in the positive electrode active material can act as a sustained-release agent, which can slowly dissolve into the electrolyte during the cycle process to replenish the consumption of the lithium salt during the cycle process, thereby improving the cycle performance of the battery; in addition, when the first lithium salt and the second lithium salt are the same, the amount of lithium salt used can be further expanded, and the negative impact of the lithium salt on the battery impedance can be reduced.

[0029] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present application. DETAILED DESCRIPTION

[0030] The terms used in this application are for the purpose of describing specific embodiments only and are not intended to limit this application. The singular forms of "a", "said" and "the" used in this application and the appended claims are also intended to include plural forms unless the context clearly indicates other meanings. It should also be understood that the term "and / or" used herein refers to and includes any or all possible combinations of one or more associated listed items.

[0031] It should be understood that although the terms "first", "second", "third", etc. may be used in this application to describe various information, this information should not be limited to these terms. These terms are only used to distinguish the same type of information from each other. For example, without departing from the scope of this application, the first information may also be referred to as the second information, and similarly, the second information may also be referred to as the first information. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of this application, the meaning of "multiple" is two or more, unless otherwise clearly and specifically defined.

[0032] In the related art, when the battery is under high voltage, the positive electrode active material will strengthen the oxidation of the electrolyte, the high temperature performance of the battery will seriously deteriorate, and the long cycle life cannot be guaranteed. In particular, during the long-term cycle charge and discharge process under high voltage, the volume of the positive electrode material will expand and cause serious cracks, and the solvent in the electrolyte will enter the interior of the positive electrode material, causing problems such as oxidation of the electrolyte and gas production, and ultimately causing serious capacity decay. The degradation of electrochemical performance will be further aggravated in a high temperature environment. In a low temperature working environment, the viscosity of the electrolyte will increase, resulting in a slower lithium ion migration rate and an increase in the battery interface impedance, which will reduce the conductivity of the battery, and ultimately lead to a decrease in the low temperature discharge performance of the battery.

[0033] In view of the above problems, an embodiment of the present application provides a battery, which includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, the positive electrode active material layer includes a positive electrode active material, a conductive agent, a binder and a positive electrode additive, and the positive electrode additive includes a first lithium salt;

[0034] The electrolyte includes an organic solvent, an electrolyte lithium salt and an electrolyte additive. The electrolyte lithium salt or the electrolyte additive includes a second lithium salt, which is the same as or different from the first lithium salt.

[0035] Among them, the present application does not limit the selection of the positive electrode current collector, for example, the positive electrode current collector can be aluminum foil. The present application does not limit the selection of the positive electrode active material, which can be selected according to actual needs, for example, lithium transition metal oxides can be used as positive electrode active materials. The conductive agent and the binder in the positive electrode active material layer of the present application can be selected from conventional materials in the field. The positive electrode additive of the present application includes a first lithium salt.

[0036] The present application does not limit the composition of the negative electrode sheet, which can be selected according to actual needs. For example, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, and the negative electrode active material layer includes a negative electrode active material, a conductive agent, and a binder. The separator of the present application can be selected from conventional materials in the art.

[0037] The electrolyte of the present application includes an organic solvent, an electrolyte lithium salt and an electrolyte additive. The present application does not limit the selection of the organic solvent, and the organic solvent can be selected according to actual needs, as long as the electrolyte lithium salt and the electrolyte additive can be fully dissolved and have high stability. The electrolyte lithium salt or electrolyte additive of the present application includes a second lithium salt, which can be the same as the first lithium salt or different from the first lithium salt.

[0038] According to the above scheme provided by the present application, after the positive electrode sheet and the electrolyte are applied to the lithium-ion battery, the lithium-ion battery has excellent high-temperature cycle performance, high-temperature storage performance and low-temperature discharge performance. This is because when the first lithium salt is added to the positive electrode sheet, the first lithium salt can decompose on the surface of the positive electrode active material layer to produce lithium-containing compounds. These substances can participate in the construction of the CEI film, effectively improving the thermal stability, toughness and lithium conductivity of the CEI film, thereby reducing the side reactions between the positive electrode active material and the electrolyte, avoiding the dissolution and structural destruction of the positive electrode active material, and preventing the oxidation and gas production of the electrolyte, thereby improving the battery's cycle performance and storage performance and thermal safety performance at high temperatures. At the same time, the lithium fluoride rich in the CEI film can enhance the rapid transmission of lithium ions on the positive electrode surface and improve the low-temperature performance of the battery; when the second lithium salt is added to the electrolyte, the second lithium salt not only participates in the construction of the CEI film, but also participates in the construction of the SEI film, thereby simultaneously improving the thermal stability of the battery's CEI film and SEI film. The invention relates to a novel battery which can improve the quality of the battery and the performance of the battery. The invention relates to a battery which can improve the quality of the battery and the performance of the battery. The invention relates to a battery which can improve the quality of the battery and the performance of the battery. The invention relates to a battery which can improve the quality of the battery and the performance of the battery. The invention relates to a battery which can improve the quality of the battery and the performance of the battery. The invention relates to a battery which can improve the quality of the battery and the performance of the battery. The invention relates to a battery which can improve the quality of the battery and the performance of the battery. The invention relates to a battery which can improve the quality of the battery and the performance of the battery. The invention relates to a battery which can improve the quality of the battery and the performance of the battery.

[0039] In a specific embodiment, the second lithium salt is the same as the first lithium salt, the electrolyte lithium salt includes the second lithium salt, and the second lithium salt includes lithium hexafluorophosphate.

[0040] In a specific embodiment, the electrolyte additive includes a second lithium salt, and the second lithium salt includes lithium difluorophosphate, lithium fluoride, lithium bis(oxalatoborate) (LiBOB), lithium tetrafluoroborate (LiBF 4), lithium difluorobisoxalate borate (LiODFB), lithium difluorobisoxalate phosphate (LiODFP), lithium tetrafluorobisoxalate phosphate (LiTFOP), lithium carbonate, lithium nitrate, lithium phytate, 4,5-dicyano-2-trifluoromethyl imidazole lithium (LiTDI), lithium hexafluoroarsenate, lithium perchlorate, trifluorosulfonyl lithium, bistrifluoromethylsulfonyl imide lithium (LiTFSI), tris (trifluoromethylsulfonyl) methyl lithium, bisfluorosulfonyl imide lithium (LiFSI) at least one. When the second lithium salt is selected from the above lithium salts, the lithium salt can participate in the construction of the CEI film on the surface of the positive electrode active material layer, and can also participate in the construction of the SEI film, thereby simultaneously improving the thermal stability, toughness and lithium conductivity of the CEI film and SEI film of the battery, reducing the probability of side reactions between the electrolyte and the positive and negative electrode active materials, and improving the transmission rate and migration rate of lithium ions, thereby improving the high and low temperature performance of the battery.

[0041] In a preferred embodiment, the second lithium salt includes at least one of lithium difluorophosphate, lithium bis(oxalatoborate), lithium tetrafluoroborate, lithium difluorobis(oxalatoborate), lithium difluorobis(oxalatophosphate), lithium tetrafluorobis(oxalatophosphate), 4,5-dicyano-2-trifluoromethylimidazolium lithium, lithium bis(trifluoromethylsulfonyl)imide, and tris(trifluoromethylsulfonyl)methyl lithium. When the second lithium salt is within the above preferred range, the second lithium salt can be better dissolved in the electrolyte, avoiding the precipitation or precipitation of the second lithium salt in the electrolyte, and giving full play to the electrochemical effect of the second lithium salt.

[0042] In a specific embodiment, the mass percentage of the first lithium salt in the positive electrode active material layer is 0.01% to 1%, for example, the mass percentage of the first lithium salt in the positive electrode active material layer can be 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1%, etc. When the mass percentage of the first lithium salt is within the above range, the sufficient amount of lithium-containing compounds and other substances produced by the decomposition of the first lithium salt can effectively improve the thermal stability, toughness and lithium conductivity of the CEI film, avoiding the insufficient improvement of the thermal stability, toughness and lithium conductivity of the CEI film due to the small amount of lithium-containing compounds and other substances, thereby further improving the high and low temperature performance of the battery.

[0043] In a specific embodiment, the mass percentage of the second lithium salt in the electrolyte is 0.01% to 1%, for example, the mass percentage of the second lithium salt in the electrolyte can be 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1%, etc. When the mass percentage of the second lithium salt is within the above range, the second lithium salt can be completely dissolved in the electrolyte, participate in the construction of the SEI film and the CEI film, further improve the stability and lithium conductivity of the SEI film and the CEI film, and make the high and low temperature performance of the battery higher.

[0044] In a specific embodiment, the electrolyte additive also includes a cyclic additive. The cyclic additive of the present application refers to a compound having two or more ring structures, which are connected by chemical bonds and can be aromatic rings (such as benzene rings) or other heterocyclic rings. When a cyclic additive is added to the electrolyte, the cyclic additive can synergize with the lithium salt to construct a CEI film and SEI film with high stability, so that the structure of the positive electrode active material can be better stabilized, the dissolution of transition metal ions can be reduced, the side reaction of the positive electrode active material and the electrolyte can be avoided, and the decomposition and gas production of the electrolyte can be reduced, so that the high temperature cycle performance, high temperature storage performance and thermal safety performance of the lithium ion battery can be improved to a greater extent; at the same time, the lithium salt and the cyclic additive synergistically act to reduce the negative effect of the cyclic additive on the battery impedance when it is used alone, thereby improving the transmission rate and migration rate of lithium ions in the battery, reducing the impedance of the battery, and making the battery take into account both high and low temperature performance.

[0045] In a specific embodiment, the cyclic additive includes at least one of the compounds shown in structural formula 1-1 to structural formula 1-6:

[0046]

[0047]

[0048] The cyclic additives of the present application include five-membered cyclic carbonate groups and / or five-membered cyclic sulfate groups. The sulfate groups or carbonate groups in the cyclic additives can participate in the formation of the interface film and improve the stability of the interface film. When the cyclic additives are selected from the above compounds, the cyclic additives and lithium salts can better synergize to generate CEI films and SEI films with higher stability, thereby better stabilizing the structure of the positive electrode active material, reducing the decomposition and gas production of the electrolyte, and making the high-temperature cycle performance, high-temperature storage performance and thermal safety performance of the lithium-ion battery higher; and the transmission rate and migration rate of the lithium ions of the battery are higher, improving the low-temperature performance of the battery.

[0049] In a specific embodiment, the mass percentage of the cyclic additive in the electrolyte is 0.1% to 4%, for example, the mass percentage of the cyclic additive in the electrolyte can be 0.1%, 0.2%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5% or 4%, etc. When the mass percentage of the cyclic additive is within the above range, the cyclic additive can better improve the stability of the CEI film and the SEI film, improve the stability of the positive and negative electrode active materials, avoid structural changes in the positive and negative electrode active materials and decomposition and gas production of the electrolyte on the surface of the positive and negative electrode active materials, thereby better improving the high temperature performance of the battery, and at the same time, it can avoid excessive impedance of the battery caused by too much cyclic additive, thereby balancing the high and low temperature performance of the battery.

[0050] In a specific embodiment, the first lithium salt, the second lithium salt and the cyclic additive satisfy the following relationship:

[0051] 0.01≤M b / M a1 ≤400;

[0052] and / or, 0.005≤M b / (M a1 +M a2 )≤200

[0053] Among them, the mass percentage of the cyclic additive in the electrolyte is M b %, and the mass percentage of the first lithium salt in the positive electrode active material layer is M a1 %, and the mass percentage of the second lithium salt in the electrolyte is M a2 %.

[0054] It is understandable that the above M b / M a1 、M b / (M a1 +M a2 ) must meet at least one of the following formulas, or both. a1 is the mass percentage of the first lithium salt in the positive electrode active material layer, M a2 is the mass percentage of the second lithium salt in the electrolyte, M b is the mass percentage of the cyclic additive in the electrolyte, therefore, M a1 +M a2 Refers to the mass percentage of lithium salt in the entire battery. Therefore, based on experience and experimental findings, M b / M a1 The physical meaning of M is the matching degree between the cyclized additives in the battery electrolyte and the lithium salt in the positive electrode; b / (M a1 +M a2) is the physical meaning of the matching degree between the cyclic additives in the battery electrolyte and the lithium salt in the entire battery. b / M a1 、M b / (M a1 +M a2 ) is within the above range, the lithium salt and the cyclic additives work synergistically to form SEI and CEI films with high stability, toughness and lithium conductivity, improve the stability of positive and negative electrode active materials, reduce the probability of side reactions between the electrolyte and the positive and negative electrode active materials, avoid decomposition and gas production of the electrolyte and structural changes of the positive and negative electrode active materials, and improve the transmission rate and migration rate of lithium ions, thereby further improving the high and low temperature performance of the battery. b / M a1 <0.01 and / or M b / (M a1 +M a2 )<0.005, the ratio of the cyclic additive to the lithium salt is small, resulting in insufficient improvement in the thermal stability and toughness of the SEI film and CEI film, resulting in poor improvement in the high temperature performance and thermal safety performance of the battery, and the structural change of the positive electrode active material will also deteriorate the energy density of the battery to a certain extent. b / M a1 >400 and / or Mb / (M a1 +M a2 )>200, the ratio of the cyclic additive to the lithium salt is too large, resulting in poor lithium conductivity of the formed SEI film and CEI film, which reduces the migration rate of lithium ions, degrades the impedance of the battery, and leads to poor low-temperature performance of the battery.

[0055] In a specific embodiment, the first lithium salt, the second lithium salt and the cyclic additive satisfy the following relationship:

[0056] 5≤M b / M a1 ≤60;

[0057] and / or, 0.22≤M b / (M a1 +M a2 )≤12.

[0058] When M b / M a1 、M b / (M a1 +M a2) is within the above range, the lithium salt and the cyclic additives can work together better, and the stability, toughness and lithium conductivity of the generated SEI film and CEI film are better, making the stability of the positive and negative electrode active materials higher, while improving the transmission rate and migration rate of lithium ions, thereby improving the high and low temperature performance of the battery.

[0059] In a specific embodiment, 0.01≤M a1 ≤1, for example, M a1 is 0.01, 0.05, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 1, etc.; and / or, 0.01≤M a2 ≤1, for example, M a2 is 0.01, 0.05, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 1, etc.; and / or, 0.1≤M b ≤4, for example, M b 0.1, 0.5, 1, 1.5, 2, 2.5, 3, 3.5 or 4, etc. When the mass percentage of the first lithium salt in the positive electrode active material layer, the mass percentage of the second lithium salt in the electrolyte, and the mass percentage of the cyclic additive in the electrolyte are within the above ranges, the lithium salt and the cyclic additive can have a better synergistic effect, and the constructed SEI film and CEI film have excellent stability, toughness and lithium conductivity, improve the stability of the positive and negative electrode active materials, reduce the probability of side reactions between the electrolyte and the positive and negative electrode active materials, and improve the transmission rate and migration rate of lithium ions, thereby further improving the high and low temperature performance of the battery.

[0060] In a specific embodiment, the electrolyte further includes fluorocarbonate, and the fluorocarbonate includes at least one of fluoroethylene carbonate, difluoroethylene carbonate (DFEC), and fluoroethylene carbonate, and the mass percentage of the fluorocarbonate in the electrolyte is 0.3% to 15%. Preferably, the fluorocarbonate includes fluoroethylene carbonate. When the selection and mass percentage of the fluorocarbonate are within the above range, the fluorocarbonate can synergize with lithium salts and cyclic additives to further improve the stability and lithium conductivity of the SEI film, thereby better protecting the negative electrode active material and the electrolyte, avoiding side reactions of the negative electrode active material and the electrolyte, and making the high and low temperature performance of the battery better.

[0061] In a specific embodiment, the electrolyte includes an electrolyte lithium salt, and the electrolyte lithium salt includes an organic lithium salt and / or an inorganic lithium salt. Preferably, the electrolyte lithium salt is selected from at least one of compounds containing fluorine and lithium elements. More preferably, the electrolyte lithium salt is selected from at least one of hexafluorophosphate, hexafluoroarsenate, perchlorate, trifluorosulfonyl lithium, bistrifluoromethylsulfonyl imide lithium, tris (trifluoromethylsulfonyl) methyl lithium, and bisfluorosulfonyl imide lithium. The molar concentration of the electrolyte lithium salt in the electrolyte is 0.5M to 1.5M, for example, 0.5M, 0.6M, 0.7M, 0.8M, 0.9M, 1M, 1.1M, 1.2M, 1.3M, 1.4M or 1.5M, etc. When the selection of the electrolyte lithium salt and the molar concentration are within the above range, the conductivity and stability of the electrolyte can be further improved, thereby further improving the high and low temperature performance of the battery. If the molar concentration of the electrolyte lithium salt is too low, the conductivity of the electrolyte is low, resulting in deterioration of the battery's cycle performance; if the molar concentration of the electrolyte lithium salt is too high, the viscosity of the electrolyte is too high, the lithium ion migration rate is reduced, and the battery's rate performance is reduced. Preferably, the molar concentration of the electrolyte lithium salt in the electrolyte is 0.8M to 1.3M.

[0062] In a specific embodiment, the electrolyte includes an organic solvent, and the organic solvent includes at least two of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl formate, ethyl formate, ethyl propionate, propyl propionate, methyl butyrate, and tetrahydrofuran. When the organic solvent of the electrolyte is selected from the above organic solvents, the viscosity of the electrolyte is lower and the ion conductivity is higher, which is conducive to improving the migration rate of lithium ions, and the above organic solvent can improve the stability of the electrolyte and avoid the decomposition reaction of the electrolyte, thereby further improving the high and low temperature performance of the battery.

[0063] In a specific embodiment, the positive electrode active material layer further includes a positive electrode active material, and the positive electrode active material includes at least one of lithium cobalt oxide, lithium nickel manganese cobalt ternary material, lithium iron phosphate, and lithium manganese oxide. When the positive electrode active material is selected from the above compounds, the positive electrode active material can give full play to its performance and improve the electrochemical performance of the battery.

[0064] In a specific embodiment, the battery further includes a negative electrode sheet, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on the surface of the negative electrode current collector, the negative electrode active material layer includes a negative electrode active material, a conductive agent and a binder. The negative electrode active material includes natural graphite, artificial graphite, mesophase microcarbon beads (abbreviated as MCMB), hard carbon, soft carbon, silicon, silicon-carbon composite, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO 2 , spinel-structured lithiated TiO 2 -Li 4 Ti 5 O 12, Li-Al alloy.

[0065] The embodiments of the present application have no particular restrictions on the negative electrode current collector, as long as the purpose of the present application can be achieved, for example, it can be copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, foam nickel, foam copper or a composite current collector.

[0066] The conductive agent and the binder in the negative electrode active material layer of the embodiment of the present application can be selected from conventional materials in the art.

[0067] In a specific embodiment, the battery also includes a diaphragm. The embodiment of the present application has no particular restrictions on the material and shape of the diaphragm, as long as it does not significantly damage the effect of the present application. It may include porous sheet-like or non-woven fabric-like materials with excellent liquid retention, etc. The materials of the resin or glass fiber diaphragm include but are not limited to polyolefins, aromatic polyamides, polytetrafluoroethylene, polyether sulfone, etc., and can be specifically set according to needs.

[0068] The second aspect of the present application provides an electronic device, comprising the above-mentioned battery. The electronic device has the advantages corresponding to the above-mentioned battery, which will not be described in detail.

[0069] The electronic devices of the embodiments of the present application may be conventional electronic devices in the art. By way of example, the electronic devices may include mobile devices (such as mobile phones, laptop computers, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., without particular limitation.

[0070] Hereinafter, the present application will be further described in detail through specific embodiments.

[0071] Example 1

[0072] 1. Preparation of positive electrode

[0073] The positive electrode active material NCM622 and the first lithium salt (the type and amount of the additives are shown in Table 1), the conductive agent CNT, and the binder polyvinylidene fluoride are mixed in a weight ratio of (97-M a1 ):M a1 :1.5:1.5 is fully stirred and mixed in N-methylpyrrolidone solvent to form a uniform positive electrode slurry. The positive electrode slurry is coated on the positive electrode current collector aluminum foil, dried, and cold pressed to obtain a positive electrode sheet.

[0074] 2. Preparation of negative electrode sheet

[0075] The negative electrode active material graphite, the conductive agent acetylene black, the binder styrene butadiene rubber, and the thickener sodium carboxymethyl cellulose are fully stirred and mixed in a proper amount of deionized water solvent at a mass ratio of 95:2:2:1 to form a uniform negative electrode slurry. The negative electrode slurry is coated on the negative electrode current collector copper foil, dried, and cold pressed to obtain a negative electrode sheet.

[0076] 3. Preparation of electrolyte

[0077] Ethylene carbonate (EC), propylene carbonate (PC), and diethyl carbonate (DEC) were mixed and stirred in a mass ratio of 2:1:7 to form a mixed solvent, 2% fluoroethylene carbonate (FEC) was added, and lithium hexafluorophosphate (LiPF 6 ) are mixed evenly to obtain LiPF 6 A mixed solution with a molar concentration of 1.1 M; then, based on the total mass of the electrolyte, a second lithium salt and a cyclic additive (the type and amount of the additive are shown in Table 1) were added to obtain the electrolytes of the embodiments and comparative examples.

[0078] 4. Production of lithium-ion batteries

[0079] The positive electrode sheet, separator and negative electrode sheet are wound to obtain a bare cell. The bare cell is placed in the aluminum-plastic film that has been punched to complete the top and side sealing. After high-temperature baking, the prepared electrolyte is injected, and then the battery is completed after standing, forming, volume separation, testing and other processes.

[0080] The preparation methods of the batteries provided in Examples 2 to 38 and Comparative Examples 1 to 14 are substantially the same as that in Example 1, and the specific parameters are shown in Table 1.

[0081] Table 1

[0082]

[0083]

[0084]

[0085]

[0086]

[0087] Test example

[0088] Battery performance test:

[0089] 45℃ cycle test: Place the battery in a 45±2℃ environment, and perform standard charge and discharge cycles at a cycle rate of 1C and a charging voltage of 3.0-4.3V. Calculate the capacity retention rate of the battery after 700 cycles. The calculation formula is as follows: 700th cycle capacity retention rate (%) = (700th cycle discharge capacity) / (first cycle discharge capacity)*100%. The results are recorded in Table 2.

[0090] 85℃ storage test: Charge the divided battery cells to 4.3V at 0.5C current at room temperature, place the fully charged battery in an 85℃ environment for 12 hours, and measure the thickness expansion rate (%) = (cycle thickness after storage - thickness before storage) / (thickness before cycle) * 100%. After returning to room temperature, discharge the battery cells to 3.0V at 0.5C current, and record the discharge capacity. Capacity retention rate (%) = (capacity of the first cycle of discharge after storage) / (capacity before storage) * 100%.

[0091] -20℃ low temperature discharge test: Fully charge the battery at 1.0C at 25℃, cut-off current 0.05C, let stand for 10min, discharge at 0.2C to 3.0V at 25℃, repeat charge and discharge for 3 weeks, record the discharge capacity at 0.2C in the third week and use it as the initial capacity. Fully charge the battery at 1.0C at 25℃, cut-off current 0.05C. Let stand at -20℃ for 4H, then discharge at 0.2C to 3.0V, record the discharge capacity. The calculation formula is as follows: -20℃ discharge capacity retention rate (%) = (discharge capacity) / (initial capacity)*100%, the results are recorded in Table 2.

[0092] 130℃ thermal shock test: Test method: Place the battery in a 25±2℃ environment, follow the standard charge and discharge cycle, cycle rate 1C, and place it in an oven after full charge. The oven is heated to 130℃ at 5±2℃ / min and kept for 1h before stopping. Record whether it catches fire or explodes. YES means it catches fire or explodes, and NO means it does not catch fire or explode. The results are recorded in Table 2.

[0093] Table 2

[0094]

[0095]

[0096]

[0097] It can be seen from Table 2 that, according to the comparison between Comparative Example 1 and Comparative Example 3, and Comparative Example 2 and Comparative Example 4, adding lithium salt to the positive electrode active material layer can effectively improve the high and low temperature performance of the battery.

[0098] According to the comparison between Comparative Example 3 and Example 1, adding lithium salt to the positive electrode active material layer and the electrolyte at the same time can effectively improve the high and low temperature performance of the battery.

[0099] According to the comparison between Example 2 and Example 1 and Comparative Examples 1 to 6, when the positive electrode active material layer includes lithium salt and the electrolyte includes lithium salt and cyclic additives, the lithium salt and cyclic additives can act synergistically to improve the high and low temperature performance of the battery.

[0100] According to the comparison of Examples 2 to 11, when the lithium salt is selected from the above compounds, the high and low temperature performance of the battery can be improved.

[0101] According to the comparison of Examples 2, 12 to 16 and Comparative Examples 7 and 8, it can be seen that as the mass percentage of lithium salt in the positive electrode active material layer increases, the high and low temperature performance of the battery improves accordingly. When the mass percentage of lithium salt reaches 0.1%, the high and low temperature performance of the battery reaches the highest, and then the high and low temperature performance of the battery decreases as the content of lithium salt increases, while the thermal safety performance of the battery has been improved as the content of lithium salt increases. In addition, when the mass percentage of lithium salt in the positive electrode active material layer is in the range of 0.01% to 1%, the high and low temperature performance of the battery is better balanced.

[0102] According to the comparison of Examples 2, 17 to 21 and Comparative Examples 9 and 10, as the mass percentage of lithium salt in the electrolyte increases, the high and low temperature performance of the battery is improved, and the thermal safety performance of the battery is improved. When the mass percentage of lithium salt in the electrolyte is within the range of 0.01% to 1%, the high and low temperature performance of the battery is better balanced.

[0103] According to the comparison of Examples 2 and 22 to 26, when the lithium salt is selected from the compounds represented by Formula 1-1 to Formula 1-6, the high and low temperature performance of the battery can be better improved.

[0104] According to the comparison of Examples 2, 27 to 32 and Comparative Examples 11 and 12, as the mass percentage of the cyclic additive in the electrolyte increases, the high temperature performance of the battery improves, while the low temperature performance and thermal safety performance of the battery decrease. When the mass percentage of the cyclic additive in the electrolyte is within the range of 0.1% to 4%, the high and low temperature performance of the battery is better.

[0105] According to the comparison between Examples 2 to 38 and Comparative Examples 13 and 14, when 0.01≤M b / M a1 ≤400 and / or 0.005≤M b / (M a1 +M a2)≤200, the battery can have excellent high and low temperature performance; according to the comparison of Examples 2, 11 to 14 with Example 15, the comparison of Examples 2, 20 to 21 with Examples 17 to 19, the comparison of Examples 2, 28 to 32 with Example 31, the comparison of Example 36 with Examples 34 to 35, and Examples 37 to 38, when 5≤M b / M a1 ≤60 and / or 0.22≤M b / (M a1 +M a2 )≤12, the lithium salt and the cyclic additives can work better synergistically, making the high and low temperature performance of the battery higher.

[0106] The embodiments of the present application have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The selection of terms used herein is intended to best explain the principles of the embodiments, practical applications, or improvements to the technology in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.

Claims

1. A battery, characterized in that: The battery comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, the positive electrode active material layer comprises a positive electrode active material, a conductive agent, a binder and a positive electrode additive, and the positive electrode additive comprises a first lithium salt; The electrolyte includes an organic solvent, an electrolyte lithium salt and an electrolyte additive. The electrolyte lithium salt or the electrolyte additive includes a second lithium salt, which is the same as or different from the first lithium salt.

2. The battery according to claim 1, characterized in that The second lithium salt is the same as the first lithium salt; The electrolyte lithium salt includes a second lithium salt, and the second lithium salt includes lithium hexafluorophosphate; and / or, The electrolyte additive includes a second lithium salt, and the second lithium salt includes at least one of lithium difluorophosphate, lithium fluoride, lithium bis(oxalatoborate), lithium tetrafluoroborate, lithium difluorobis(oxalatoborate), lithium difluorobis(oxalatophosphate), lithium tetrafluorobis(oxalatophosphate), lithium carbonate, lithium nitrate, lithium phytate, 4,5-dicyano-2-trifluoromethylimidazole lithium, lithium hexafluoroarsenate, lithium perchlorate, trifluorosulfonyl lithium, bis(trifluoromethylsulfonyl)methyl lithium, and bis(fluorosulfonyl)imide lithium.

3. The battery according to claim 2, characterized in that The second lithium salt includes at least one of lithium difluorophosphate, lithium bis(oxalatoborate), lithium tetrafluoroborate, lithium difluorobis(oxalatoborate), lithium difluorobis(oxalatophosphate), lithium tetrafluorobis(oxalatophosphate), lithium 4,5-dicyano-2-trifluoromethylimidazole, lithium bis(trifluoromethylsulfonyl)imide, and tris(trifluoromethylsulfonyl)methyllithium.

4. The battery according to claim 1, characterized in that The mass percentage of the first lithium salt in the positive electrode active material layer is 0.01% to 1%; and / or, The mass percentage of the second lithium salt in the electrolyte is 0.01% to 1%.

5. The battery according to claim 1, characterized in that The electrolyte additives also include cyclic additives.

6. The battery according to claim 5, characterized in that The cyclic additive includes at least one of the compounds shown in structural formula 1-1 to structural formula 1-6: And / or, the mass percentage of the cyclic additive in the electrolyte is 0.1% to 4%.

7. The battery according to claim 5, characterized in that The first lithium salt, the second lithium salt and the cyclic additive satisfy the following relationship: 0.01≤M b / M a1 ≤400; and / or, 0.005≤M b / (M a1 +M a2 )≤200 Wherein, the mass percentage of the cyclic additive in the electrolyte is M b %, and the mass percentage of the first lithium salt in the positive electrode active material layer is M a1 %, and the mass percentage of the second lithium salt in the electrolyte is M a2 %.

8. The battery according to claim 7, characterized in that The first lithium salt, the second lithium salt and the cyclic additive satisfy the following relationship: 5≤M b / M a1 ≤60; and / or, 0.22≤M b / (M a1 +M a2 )≤12.

9. The battery according to claim 7 or 8, characterized in that: 0.01≤M a1 ≤1; and / or, 0.01≤M a2 ≤1; and / or, 0.1≤M b ≤4.

10. An electronic device, characterized in that: A battery comprising the battery according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Lithium-ion battery positive pole piece and preparation method thereof

    CN112151807A

  • Lithium ion battery

    CN115692825A

  • Lithium ion battery

    CN117080557A

  • Lithium ion battery and preparation method thereof

    CN119009172A

  • Additive for lithium-ion battery, lithium-ion battery, and electrical device

    WO2024131239A1